2014
DOI: 10.1016/j.jpedsurg.2014.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Is early delivery beneficial in gastroschisis?

Abstract: Early delivery is associated with prolonged ENT/LOS, suggesting elective delivery at <37weeks is not beneficial. Combined IABD/EABD or IABD/collapsed extra-abdominal bowel is suggestive of complex gastroschisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 28 publications
5
35
2
5
Order By: Relevance
“…Interestingly, in 2 cases, IABD seen during the second trimester regressed spontaneously, advocating for caution when interpreting this ultrasound finding early in pregnancy. In our cohort, we were not able to confirm the findings by Carnaghan et al [37], showing an increased predictive value when combining intra- and extra-abdominal loop assessment. It has been hypothesized that antenatal bowel dilatation is secondary to constriction at the defect site [38] and/or inflammatory changes of the intestinal bowel wall changes secondary to exposure to amniotic fluid constituents [28,39,40,41].…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, in 2 cases, IABD seen during the second trimester regressed spontaneously, advocating for caution when interpreting this ultrasound finding early in pregnancy. In our cohort, we were not able to confirm the findings by Carnaghan et al [37], showing an increased predictive value when combining intra- and extra-abdominal loop assessment. It has been hypothesized that antenatal bowel dilatation is secondary to constriction at the defect site [38] and/or inflammatory changes of the intestinal bowel wall changes secondary to exposure to amniotic fluid constituents [28,39,40,41].…”
Section: Discussioncontrasting
confidence: 99%
“…26,27 The results of other studies are not consistent with this latter observation. 28,29 In our study, results showed a tendency that correlated shorter survival with a lower birth weight when specifically examining esophageal atresia and myelomeningocele; however, this association was not statistically significant. As per the bibliography, low birth weight is a risk factor for the survival of newborn infants with CAs.…”
Section: Discussioncontrasting
confidence: 63%
“…Concordant with the presented course, it has been described that the presence of meconium or blood-stained amniotic fluid and either prenatal or postnatal gastrointestinal complications is associated with an older age to reach full enteral feeds [16]. Therefore, the reported infant suffered from type 2 intestinal failure, requiring >28 days of parenteral nutrition [15].…”
Section: Discussionsupporting
confidence: 61%
“…Early elective delivery for suspected complex cases of gastroschisis is normally advocated in order to prevent the development of bowel necrosis secondary to the abdominal events. However, a recently published multi-institutional study did not reveal any benefit to the elective delivery at <37 weeks of gestation [15].…”
Section: Discussionmentioning
confidence: 91%